A retrospective study to assess the epidemiological and economic burden of pneumococcal diseases in adults aged 50 years and older in Taiwan. (May 2014) - Wu, David Bin-Chia; Roberts, Craig S.; Huang, Yhu-Chering; Chien, Ling; Fang, Chi-Hui; Chang, Chee Jen
Abstract Objective: Invasive pneumococcal disease (IPD) and pneumococcal pneumonia cause substantial morbidity and mortality worldwide. This retrospective study was conducted to estimate the disease burden from pneumococcal disease in older adults in Taiwan from a health insurer's perspective. Methods: Data for the years 2002–2009 from patients aged ≥50 years with insurance records indicating pneumococcal meningitis, pneumococcal bacteremia, or hospitalized or outpatient pneumonia were obtained from the National Health Insurance Research Database in Taiwan. Admission data for inpatients, visit data for outpatients, and associated costs were extracted from the database to estimate the incidence, case fatality rates, and direct and indirect costs of pneumococcal disease episodes. These data were applied to the estimated population of Taiwan in 2010 to provide an estimated disease burden for a single year from the payer perspective. Results: The average incidence per 100, 000 person years was 2.4 for IPD, 278.8 for hospitalized pneumococcal pneumonia, and 1376.4 for outpatient pneumococcal pneumonia. The average case fatality rate was 12.3% for IPD and 10.0% for hospitalized pneumonia. Hospitalized pneumonia accounted for over 90% of direct medical costs. The incidence of hospitalized pneumococcal pneumonia per 100, 000 person years was 84.4 for adults of 50–64 years, 313.1 for adults of 65–74 years, 820.3 for adults of 75–84 years, and 1650.9 for adults of 85+ year of age. In 2010, it was estimated there were over 113, 000 episodes of pneumococcal disease, causing almost 2000 deaths, with direct medical costs of more than NT3.4 billion annually. Conclusions: Pneumococcal disease is a significant cause of mortality and excess healthcare expense among the elderly in Taiwan. Disease burden in older adults increases with advancing age.